Frequent attenders at risk of disability pension: a longitudinal study combining routine and register data - Reho, Tiia T.M. (Scand J Public Health, 2019)
Aims: Frequent attendance in healthcare services is associated with ill-health and chronic illnesses. More information is needed about the phenomenon’s connection with disability pensions (DPs). Methods: The study group comprised 59,676 patients divided into occasional- (1yFAs) and persistent frequent attenders (pFAs) and non-frequent attenders (non-FAs). Odds ratios for DP were analysed for these groups taking into account preceding sickness absence days. The awarded DPs were obtained from the Finnish Centre for Pensions and data on primary care visits were obtained from Pihlajalinna, a nationwide occupational healthcare provider. Results: 1yFAs and pFAs have more DPs than non-FAs. During follow-up, 14.9% of pFAs, 9.6% of 1yFAs and 1.6% of non-FAs had a DP decision of any kind. pFAs receive more partial and fixed-term decisions than the other groups and most permanent DPs are granted to 1yFAs. Musculoskeletal disorders are the most common reason for illness-based retirement in all groups but 1yFAs and pFAs have proportionally more mental disorders leading to DP. The group of non-FAs, on the other hand, has more DPs granted based on neoplasms. Both 1yFAs and pFAs have an increased risk of DP but the effect is diluted after taking into account preceding sick-leave. Conclusions: Frequent attendance of healthcare services, both occasional and persistent, is associated with increased risk of future DP. The association is linked to increased sickness absences. Frequent attenders should be identified and their rehabilitative needs evaluated. Frequency of consultation could be used in selecting candidates for early rehabilitation before sickness absences develop.